Renal vascular variations, split renal function and donor preferences:chalenge and crossroads towards right kidney choice - Stefan Filipovski; Irena Rambabova Busljetic; Igor Nikolov; Galina Severova Andreevska; Zhaklina Shterjova Markovska; Adrijana Spasovska; Vlatko Karanfilovski; Aleksandra Canevska; Mimoza Milenkova; Sabir Sulejmani; Biljana Zafirova; Saso Dohchev; et al. (Macedonian Society of Nephrology, Dialysis, Transplantation and Artifical Organs, Department of Nephrology, 2022)
Introduction. Renal vascular variations, split renal function (SRF) and potential donor’s preferences in terplay with the donation decisions in living donor kidney transplantation (LDKT). This study aimed to assess the challenges in decision for choosing an app ropriate kidney for donation. Methods. Retrospective study was performed through a review of the medical history charts and national electronic database of LDKT from 2013-2022, in one transplantation center. Those with significant missing data were excluded from the final analysis. Demographiccharacteristics, CT angiographic findings and Tc-99m DTPA renal scan for SRF and donor preferences were analysed. The bilateral presence and number of ace ssory renal arteries, their hilar or polar position in respectof the renal artery, early artery branching, variations of the vein number and left vein course were assessed. Significantly different SRF was defined as ≥10%. Results. Out of 137 consecutive LDKT, 124 donors were included in the study. The meanage of donors was 59+11 years, 40(32%) were male and 14(11%) were unrelated. There were no variations in 88(64%) renal arteries on the right and 69(56%) on the left side. The most common variation from both sides was an accessory hilar artery (15%). An accessory inferior renal polar artery was observed in 7.6% and superior in 6.4% of kidneys. Three renal arteries or three veins on one side were observed in one donor. Variation of renal arteries on both sides was 13(5.2%). Early artery branching was found in 12.9% (8%-right and 18%-left side). Two renal veins were observed in 8(3.2%) kid neys. The Nutcracker phenomenon was found in 6(4.8%). The donated kidneys in 60% was the left one and 10% were with vascular variation. In 33(27%) of donated kidneys we found at least one vascular variation. In 41(33%) of donors SRF was significantly different and in 8(18%) the better kidney was donated due to the donor preference. Conclusion. Variations in renal vascular anatomy and different SRF are very often in kidney donors. Donors preferences additionally interfere with the transplantta tion process. The quality of the decision process relies on good institutional policy and adequate pretransplant donor evaluation.
Keywords: vascualr variations; anatomy; living donor kidney transplantation; split renal function; donor preferences